2019
DOI: 10.1039/c9ta00634f
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4 nanosheets enhanced solid polymer electrolytes with excellent electrochemical performance, mechanical properties, and thermal stability

Abstract: g-C3N4 nanosheets are used as solid electrolyte filler for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(120 citation statements)
references
References 55 publications
4
115
0
1
Order By: Relevance
“…The deformation of the charge/discharge curves caused the great increase of the charge potential and the decrease of the discharge potential, and thus can be also regarded as a polarization behavior. Moreover, the deformation became more and more severe with increasing charge/ discharge cycle number or current density, consistent with the previous studies [15,56,91,92]. Actually the ANF/ PEO-FF and ANF/PEO-DF electrolyte-based cells also showed the similar yet non-severe deformation at high current densities of 0.5-1.0 C ( Fig.…”
Section: All-solid-state LI Metal Battery Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…The deformation of the charge/discharge curves caused the great increase of the charge potential and the decrease of the discharge potential, and thus can be also regarded as a polarization behavior. Moreover, the deformation became more and more severe with increasing charge/ discharge cycle number or current density, consistent with the previous studies [15,56,91,92]. Actually the ANF/ PEO-FF and ANF/PEO-DF electrolyte-based cells also showed the similar yet non-severe deformation at high current densities of 0.5-1.0 C ( Fig.…”
Section: All-solid-state LI Metal Battery Performancesupporting
confidence: 90%
“…Based on these analyses and other reports on the high stability of the LiFePO 4 cathodes [56,72], one can easily conclude that the deformation is not related to the LiFePO 4 cathode but the electrolyte. Previous studies usually ascribed to the high polarization (or severe charge/discharge curve deformation) to the increase of the internal resistance of the battery and the low Li + ion diffusivity in the solidstate electrolyte and the electrolyte/electrode interface [15,56,72,[91][92][93]. Note that all the solid-state cells exhibited much higher Coulombic efficiencies of nearly 100% during the whole cycling than the traditional LIBs with the organic liquid electrolytes (Fig.…”
Section: All-solid-state LI Metal Battery Performancementioning
confidence: 52%
See 1 more Smart Citation
“…The solid composite polymer electrolyte with 10% g-C 3 N 4 exhibited the maximum ionic conductivity (1.76 × 10 −5 S cm −1 ) at 25°C, and the conductivity reached to about 1.08 × 10 −3 S cm −1 at 100°C. And this ionic conductivity at room temperature was much higher than that of the recently reported PEO/g-C 3 N 4 /LiTFSI solid electrolytes (2.3 × 10 −6 S cm −1 , at 30°C) (Sun et al, 2019). Also this ionic conductivity is nearly close to that (2.2 × 10 −5 S cm −1 at 28°C) of the PEO based solid composite electrolyte, which needed LiTFSI as the lithium salt and 2D MXene as the filler (Pan et al, 2019).…”
Section: Resultsmentioning
confidence: 55%
“…On the other hand, Figure 9B demonstrated that the cell based on the solid composite polymer electrolyte with a capacity retention ratio of 80% after 200 cycles possessed an initial discharge capacity of 161.2 mAh g −1 , which was very close to the theoretical capacity of LiFePO 4 (170 mAh g −1 ). Moreover, this cycling performance was better than the reported LiFePO 4 /Li solid-state batteries based on PEO-LiTFSI-g-C 3 N 4 polymer electrolytes, which gave an initial discharge specific capacity of 161.3 mAh g −1 but cycled for 120 cycles at 60°C (Sun et al, 2019). The coulombic efficiency of batteries based on the solid composite polymer electrolyte during charge-discharge cycling test was as high as 99.7% in Figure 9B, which was higher than that of the battery based on the PEO-LiClO 4 electrolyte shown in Figure 9A.…”
Section: Resultsmentioning
confidence: 74%